THE COMPARISON OF DEEP NECK FLEXOR STRENGTHENING EXERICISE WITH MCKENZIE NECK EXERCISE FOR NECK POSTURE CORRECTION ON STUDENTS WITH FORWARD HEAD POSTURE AT SMA N 1 SEMARAPURA - Prasana, Gede Eka Juli; Adiputra, I Nyoman; Dinata, I Made Krisna (Majalah Ilmiah Fisioterapi Indonesia; Vol 6 No 1 (2018): Majalah Ilmiah Fisioterapi IndonesiaDO - 10.24843/MIFI.2018.v06.i01.p09, 2018)
This study aims to compare deep neck flexor strengthening exercise intervention with mckenzie neck exercise to correct the neck posture of student with forward head posture. Using experimental design with Pre-Test and Post-Test Group Design involves a sample of 24 people divided into 2 groups. Group I was given deep neck flexor strengthening exercise intervention and Group II was given mckenzie neck exercise intervention. Hypothesis Test using paired sample t-test obtained result p = 0.592 with average difference in Group I 7.58 ± 4.39 whereas Group II got difference mean 8.5 ± 3.84. These results showed no significant difference in craniovertebral angle elevation before and after intervention in both groups. Keywords : forward head posture, craniovertebrae angle, deep neck flexor strengthening exercise, mckenzie neck exercise,